ARTIFICIAL INTELLIGENCE: OPPORTUNITIES AND CHALLENGES: https://doi.org/10.5281/zenodo.15377605 - Shomurodova , Sevara; Khazratkulova, Ezoza (Journal of International science networks, 2025)
Artificial Intelligence (AI) is rapidly transforming the landscape of modern society, offering unprecedented opportunities across various sectors including healthcare, education, finance, and industry. By enabling machines to learn, adapt, and perform tasks traditionally requiring human intelligence, AI promises to enhance efficiency, decision-making, and innovation. However, the advancement of AI also introduces significant challenges, such as ethical concerns, data privacy issues, job displacement, and the risk of biased algorithms. This paper explores both the potential benefits and the pressing challenges associated with AI development and deployment, emphasizing the importance of responsible AI governance, inclusive policy-making, and sustainable technological growth.